2002
DOI: 10.1037/0022-0663.94.1.138
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interactive media on children's story memory.

Abstract: The authors examined the influence of interactive media on children's story memory. First-grade children (6 -7-year-olds) experienced a computer-based story in 1 of 4 presentation modes: One group heard only the narration, analogous to radio. A 2nd group saw an audiovisual presentation, analogous to television. A 3rd group viewed the story and interacted with animated areas of the screen. A 4th group was yoked to the interaction group such that they observed but did not control the interaction. The audio-only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 24 publications
1
43
0
2
Order By: Relevance
“…First, they ensure that encoding occurs in both verbal and visual modalities (Johnson, 1985;Murachver et al, 1996). Second, they may improve children's comprehension of the verbal material, consistent with research on the impact of pictures on children's recall of prose (Holmes, 1987;Levin et al, 1976;Ricci & Beal, 2002;Small et al, 1993). Finally, the high degree of feature overlap between the photographs and the objects in the event may maximize the likelihood of retrieval, and reinstatement, of the verbal and nonverbal preparatory information during the event itself (Tulving & Thompson, 1973).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…First, they ensure that encoding occurs in both verbal and visual modalities (Johnson, 1985;Murachver et al, 1996). Second, they may improve children's comprehension of the verbal material, consistent with research on the impact of pictures on children's recall of prose (Holmes, 1987;Levin et al, 1976;Ricci & Beal, 2002;Small et al, 1993). Finally, the high degree of feature overlap between the photographs and the objects in the event may maximize the likelihood of retrieval, and reinstatement, of the verbal and nonverbal preparatory information during the event itself (Tulving & Thompson, 1973).…”
Section: Discussionmentioning
confidence: 64%
“…SpeciWcally, children whose preparation consisted of photographs with narration (goals + narration + photographs and goals + narration + photographs + verbalization) reported more correct information than did children in both the control and goals conditions. A body of research highlights the beneWts of pictures for children's comprehension and memory of stories (Lesgold et al, 1975;Small et al, 1993); for example, Ricci and Beal (2002) found poor recall and comprehension by 6-year-olds when a story was presented verbally relative to when it was presented in both auditory and visual modalities. The current Wndings extend this research in demonstrating that, to enhance 6-year-olds' event recall, both modalities are necessary during preparation.…”
Section: Discussionmentioning
confidence: 98%
“…They may also reflect a "switch cost" (Courage et al, 2014): When attention is divided or switched among two or more tasks, some degree of dual-task inference or switch cost may result in poorer performance. However, not all studies show negative effects of children's access to irrelevant interactive hotspots and games on story memory (Homer et al, 2014;Ricci & Beal, 2002;Robb, 2010). The kinds of interactivity offered by the device in those studies may have been limited enough that children were able to focus on the story line.…”
Section: Article In Pressmentioning
confidence: 96%
“…Kamil et al (2000) described electronic books that are loaded with extraneous information as more like a game than a book reading experience. Although playful additions are designed to be interactive, motivating, and self-paced (e.g., Ricci & Beal, 2002), adding 'bells-andwhistles' to a multimedia presentation may distract children from the main activity -story comprehension -or interfere with extracting meaning from the main message (Mayer, 2001). As the human information processing system has a limited capacity (Baddeley, 1986;Sweller, 2005), sharing resources among various tasks (e.g., memorizing and integrating story events in between playing games) may come at a cost for performance (Kahneman, 1973).…”
Section: Article In Pressmentioning
confidence: 99%
“…Ricci & Beal [18] examined the influence of interactive media on children's story memory. They authors use quantitative methods to compare students' response to four story presentation conditions.…”
Section: A Technology and Literacymentioning
confidence: 99%